2021
DOI: 10.1097/ceh.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Trainers' Learning and Behaviors for Educating Health Care Professionals Using Train-the-Trainer Method: A Systematic Review and Meta-analysis

Abstract: Introduction: Train-the-trainer (TTT) programs are frequently used to facilitate knowledge dissemination. However, little is known about the effectiveness of these programs. Therefore, we sought to assess the impact of TTT programs on learning and behavior of trainers for educating health and social professionals (trainees). Methods: Guided by the Cochrane Effective Practice and Organisation of Care, we conducted a systematic review. We searched 12 data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A systematic review 16 showed how train-the-trainer programs in health care develop good trainers while training other professionals. Mostly in before and after studies, knowledge improved, however, no studies investigated the ability of trained instructors to deliver the learned program.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review 16 showed how train-the-trainer programs in health care develop good trainers while training other professionals. Mostly in before and after studies, knowledge improved, however, no studies investigated the ability of trained instructors to deliver the learned program.…”
Section: Discussionmentioning
confidence: 99%
“…is all the more necessary to generate meaningful and sustainable change in teaching practice (Berger & Thomas, 2011), one of the biggest challenges in education (Hubers, 2020). An effective strategy to increase trainers' knowledge and skills is the TTT model (Poitras et al, 2021). Often used in the health sector, this model enables potential trainers to acquire the abilities to share what they have learned with other members of their community (Ray et al, 2012).…”
Section: The Train-the-trainer Strategymentioning
confidence: 99%
“…Issue 3 also contains two systematic reviews that seek to add to the current state of the evidence in two particular CPD activities: (1) train-the-trainer programs in faculty development and (2) methodological design in quality improvement training outcomes. Poitras et al 13 assess the impact of train-the-trainer programs on learning and behavior of trainers for educating health professionals and social workers (trainees). They point to the need for more studies and the application of robust outcomes assessment models such as the New World Kirkpatrick Model to evaluate the effectiveness of train-the-trainer programs.…”
Section: Adding To the Cpd Evidence Basementioning
confidence: 99%